Family Engagement in Enhancing Children's Affection for Islamic Faith at Islamic Primary Schools in Balikpapan - Sariman, Adil; Lukman, Syaiful (Journal of Educational Research and Practice, 2024)
This study discusses "The Role of Family in Increasing Children's Love for Islam in Balikpapan City Islamic Elementary School." Through qualitative research methods, in-depth interviews were conducted to understand the dynamics of interactions between families, religious education, and children's spiritual development. The results highlight the crucial role of religious values taught in the family in shaping the moral and ethical character of children. The variety of religious practices within the family is also found to be a diverse element that enriches the spiritual experience of children. Parents are identified as moral and spiritual leaders who set an example, guide religious practice, and support a deeper understanding of religious values. The study's findings underscore the importance of the family as a key pillar of religious education, strengthening awareness of religious values within the family as a strong foundation of children's spiritual development. The implications of this research provide a basis for the development of better education and family support programs, encouraging the spiritual growth of children in Balikpapan City Islamic Primary School